Peran Kerja Nyata Pengawas Sekolah Terhadap Kinerja Guru Pendidikan Agama Islam Dalam Kegiatan Belajar Mengajar KBM Di SDN 18 Luhak Nan Duo - Siti Aisyah, S.Pd (STKIP Pesisir Selatan, 2016)
AbstractBased on the observations that have been researchers did Kepada Guru in SD 18 Luhak Nan Duo, found that teacher performance PAI in KBM still low. The purpose of this study is to Improve Teacher Performance PAI in KBM in SD 18 Luhak Nan Duo. This research is a school action. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subjects consisted of 3 people Master PAI SD 18 Luhak Nan Duo. Data were collected by using observation sheet. Data were analyzed using percentages. The results showed that the role of the real work of school inspectors can improve teacher performance PAI in KBM in SD 18 Luhak Nan Duo. This is evidenced by the increase in PAI Teacher Performance in KBM from the first cycle to the second cycle. Average Teacher Performance PAI ability in teaching in the first cycle was 49.66 with less category and the second cycle is 82.33 with both categories.Keywords: Role of Real Work superintendent of schools, teacher performance PAI, KBM.